UPDATE FOR SENIOR MANAGEMENT - BAKER,S (Tufts Archival Research Center, 2007)
Public Affairs, USA, update for senior management. Summarizes legislative activities. Lists ongoing government relations projects. Notes good news. Discusses public relations activities and public affairs administration, as well as who is in charge of the individual projects.